Summary for clinicians: ERS guidelines on pulmonary alveolar proteinosis. - Alfaro O., Tiago; McCarthy, Cormac; Bonella, Francesco; Bendstrup, Elisabeth; O'Callaghan, Marissa (Breathe, 2025)
Pulmonary alveolar proteinosis (PAP) is a rare lung disease caused by accumulation of surfactant in the alveoli, leading to debilitating respiratory symptoms and impaired gas exchange. The recent European Respiratory Society guidelines provide evidence-based recommendations for its diagnosis and management. Autoimmune PAP (aPAP) is the most common form, driven by granulocyte-macrophage colony-stimulating factor (GM-CSF) autoantibodies. Recommended diagnostic tools include bronchoalveolar lavage and quantitative GM-CSF antibody testing. Whole lung lavage and inhaled GM-CSF are first-line treatments for symptomatic or progressive aPAP. Rituximab, plasmapheresis, and lung transplantation are options for refractory disease. Referral to expert centres is advised for diagnostic and therapeutic guidance. This case-based summary for clinicians highlights the best clinical approach to patients with suspicion or confirmation of PAP.